Fraud Prevention Determinants: A Balinese Cultural Overview - Komang Adi Kurniawan Saputra; M. Mu'ah; J. Jurana; Claudia Wanda Melati Korompis; Daniel T. H. Manurung (Australasian Accounting, Business and Finance Journal, 2022)
This study aims to examine the influence of the Tri Hita Karana culture, good village governance and human resource competence on fraud prevention by being moderated by morality. Using the method of analysis, namely multiple linear regression with Moderated Regression Analysis. The total population is 133 villages, and to get the appropriate sample a random sampling technique and a total of 00 villages are sampled. This research was conducted in Tabanan-Bali Regency wich is the district with the highest number of villages and recipients of village funds in the Province of Bali. Research data collection using a questionnaire with survey techniques, the results of which are tri hita karana culture and human resource competencies have a significant positive effect on fraud prevention, while good village governance has a negative and not significant effect on fraud prevention. Another result is that the variable of morality successfully moderates the relationship between human resource competencies on fraud prevention, but is found to be unable to moderate the influence of Tri Hita Karana and good village governance on the prevention of village fund fraud.
Keywords: fraud; tri hita karana; good village governance; village funds